The Use of Picture to Improve Students’ Speaking Skill in English - Rahmi Aulia Nurdini (Department of English Language Education, UIN Sunan Ampel Surabaya, 2018)
This study is aimed to investigate how to teach English speaking or conversation interestingly for students by using a picture so that the students are easier to learn and enjoy in speaking English to others in the classroom. Method employed was descriptive qualitative method by doing observation and library research. Findings shows that using picture is one of good way to create an interesting learning process, so the students can easier to understand the lesson, and get enthusiastic to speak English to others in the classroom. Finally, if student always practice it repeatedly even out of the class, they will be able to remember permanently what they had learned and they will improve their ability in speaking English automatically.